Shakespeare on the couch : on behalf of the United Kingdom Council for Psychotherapy - Jacobs, Michael, 1941-; United Kingdom Council for Psychotherapy (London : Karnac Books, 2008)
Drawing upon a vast literature in psychoanalytic journals and either upon Shakespeare's characters themselves or alluding to those characters in the course of other topics, this book discusses eight of Shakespeare's plays and the relationships between the main characters in them.
Prologue -- The qualities of people -- Much deceived: Leontes and Othello -- Death and the maiden -- The rei(g)ns of power -- Part-objects: Prospero and Caliban -- "Father" and son: Prince Hal and Falstaff -- The Macbeths: a childless couple? -- Antony and Cleopatra: "star-cross'd" lovers? -- Epilogue.
Includes bibliographical references (pages 137-145) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- Psychology; Shakespeare, William, -- 1564-1616 -- Characters; Shakespeare, William, -- 1564-1616; Psychoanalysis and literature -- England; Drama -- Psychological aspects; Psychology in literature; Psychanalyse et littérature -- Angleterre; Théâtre (Genre littéraire) -- Aspect psychologique; Psychologie dans la littérature.; LITERARY CRITICISM -- Shakespeare; DRAMA -- Shakespeare; Psychoanalysis; Characters and characteristics; Drama -- Psychological aspects; Psychoanalysis and literature; Psychology; Psychology in literature; England